Coal energy systems - Miller, Bruce G. (Elsevier, 2005)
Coal is currently a major energy source in the United States as well as throughout the world, especially among many developing countries, and will continue to be so for many years. Fossil fuels will continue to be the dominant energy source for fueling the United States economy, with coal playing a major role for decades. Coal provides stability in price and availability, will continue to be a major source of electricity generation, will be the major source of hydrogen for the coming hydrogen economy, and has the potential to become an important source of liquid fuels. Conservation and renewable/sustainable energy are important in the overall energy picture, but will play a lesser role in helping us satisfy our energy demands. This book is a single source covering many coal-related subjects of interest ranging from explaining what coal is, where it is distributed and quantities it can be found in throughout the world, technical and policy issues regarding the use of coal, technologies used and under development for utilizing coal to produce heat, electricity, and chemicals with low environmental impact, vision for untilizing coal well into the 21st century, and the security coal presents. * Presents coal's increasing role in providing energy independence to nations * Covers current energy usage, environmental issues, and coal energy technologies * Provides a comprehensive discussion of technical and policy issues regarding the use of coal.
Title from e-book title screen (viewed Nov. 22, 2004).
Keywords: Coal.; Coal-fired power plants.; Coal-fired furnaces.; elektronické knihy; electronic books